OPTIMALISASI PERAN MENEJEMEN SUMBERDAYA MANUSIA DALAM MEMBENTUK PRILAKU KERJA BERBASIS KEPEDULIAN LINGKUNGAN (Study Kasus Institut Teknologi Dan Bisnis Diniyyah Lampung): OPTIMALISASI PERAN MENEJEMEN SUMBERDAYA MANUSIA DALAM MEMBENTUK PRILAKU KERJA BERBASIS KEPEDULIAN LINGKUNGAN (Study Kasus Institut Teknologi Dan Bisnis Diniyyah Lampung) - Junaidi, Muhammad; Sobby Kesuma, Arsyad; Kasmi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2026)
This study aims to analyze and optimize the role of Human Resource Management (HRM) in shaping environmentally conscious work behavior in organizations. Sustainability issues are a major concern for modern organizations, requiring HR management strategies that can encourage pro-environmental employee behavior. This study uses a qualitative approach with a case study method in organizations that have implemented environmentally friendly practices. Data collection techniques were carried out through in-depth interviews, observation, and documentation. The results of the study indicate that HRM optimization can be done through the integration of environmental values ​​​​in the recruitment process, training, performance appraisal, and reward systems. In addition, the role of leadership and organizational culture are key factors in shaping environmentally friendly work behavior. This study contributes to the development of sustainability-based HRM practices that can improve organizational performance while maintaining environmental sustainability This study aims to analyze and optimize the role of Human Resource Management (HRM) in shaping environmentally conscious work behavior in organizations. Sustainability issues are a major concern for modern organizations, requiring HR management strategies that can encourage pro-environmental employee behavior. This study uses a qualitative approach with a case study method in organizations that have implemented environmentally friendly practices. Data collection techniques were carried out through in-depth interviews, observation, and documentation. The results of the study indicate that HRM optimization can be done through the integration of environmental values ​​​​in the recruitment process, training, performance appraisal, and reward systems. In addition, the role of leadership and organizational culture are key factors in shaping environmentally friendly work behavior. This study contributes to the development of sustainability-based HRM practices that can improve organizational performance while maintaining environmental sustainability